The spider genus Pterotricha Kulczyński, 1903 (Araneae, Gnaphosidae) in the United Arab Emirates - Alireza Zamani (Evolutionary Systematics, 2018)
Spiders of the gnaphosid genus Pterotricha Kulczyński, 1903 occurring in the United Arab Emirates (UAE) are surveyed on the basis of a large collection deposited in the American Museum of Natural History. Within the examined material, six species were recognized, four of which are described as new to science: P. arabica sp. n. (♂♀), P. esyunini sp. n. (♂), P. nadolnyi sp. n. (♂) and P. stevensi sp. n. (♂), and two are newly recorded for the fauna of the UAE: P. dalmasi Fage, 1929 (hitherto known from Algeria, Egypt, Sudan, Israel, Jordan, Saudi Arabia, and possibly Iran) and P. kovblyuki Zamani & Marusik, 2018 (hitherto known only from Iran). Illustrations for all treated species and a map of collection localities are provided.